CLUSTERS AND INNOVATION CENTRES: IS SPECIAL LOCAL SELF-GOVERNANCE REQUIRED - T. Kovaleva (Вестник университета)
The territorial aspect of the cluster structure as a potential basis of economics advantage and as an object of the state regulation is analyzed, the approach to innovation as an integral part of the cluster model is determined, issue of direction and limits of state regulation of clusters is raised. The problems of organization of a public government model in cluster territory is discussed, the general approaches to the local self -government regulation and public government in clusters and innovation centres is highlighted.